Utilizing Whole Slide Images for the Primary Evaluation and Peer Review of a GLP-Compliant Rodent Toxicology Study. (August 2021) - Jacobsen, Matt; Lewis, Arthur; Baily, James; Fraser, Alain; Rudmann, Dan; Ryan, Shane
The approach undertaken to deliver a Good Laboratory Practice (GLP) validation of whole slide images (WSIs) and the associated workflow for the digital primary evaluation and peer review of a GLP-compliant rodent inhalation toxicity study is described. The contract research organization (CRO) undertook validation of the slide scanner, scanner software, and associated database software. This provided a GLP validated environment within the database software for the primary histopathologic evaluation using WSI and viewed with the database software web viewer. The CRO also validated a cloud-based digital pathology platform that supported the upload and transfer of WSI and metadata to a cache within the sponsor's local area network. The sponsor undertook a separate GLP validation of the same cloud-based digital pathology platform to cover the download and review of the WSI. The establishment of a fit-for-purpose GLP-compliant workflow for WSI and successful deployment for the digital primary evaluation and peer review of a large GLP toxicology study enabled flexibility in accelerated global working and potential future reuse of digitized data for advanced artificial intelligence and machine learning image analysis.